Magnetohydrodynamics - Davidson, Peter A.; Thess, Andre (International Centre for Mechanical Sciences, Courses and Lectures, 2002)
This book is an introduction to terrestial magnetohydrodynamics. It is a compendium of introductory lectures by experts in the field, focussing on applications in industry and the laboratory. A concise overview of the subject with references to further study